Collaborating in online teaching: inviting e-guests to facilitate learning in the digital environment. Issue 7 (17th June 2020) - Fulton, Crystal
Abstract : Purpose: Teaching and learning online during the Covid-19 pandemic has forced university instructors to consider online alternatives to the classroom. It is possible to facilitate students' learning in the digital environment in similar ways to the traditional face-to-face classroom. The inclusion of e-guests in the digital learning space presents one such opportunity. The purpose of this paper is to discuss the use of e-guests in online learning. Design/methodology/approach: This paper presents a case study, following a postgraduate class and the role of the e-guest in students' synchronous online learning. Findings: E-guests facilitated student learning. Their approaches to learning ranged from slides to discussions. Students responded well to this method of learning. Practical implications: There is potential for enhancing student learning through the inclusion of e-guests, who bring their expertise to the classroom. E-guests from different regions offer students an opportunity to learn from specialists they would not necessarily have access to in the traditional classroom. Originality/value: E-guests offer one important potential means of enriching online teaching.